2008
DOI: 10.5045/kjh.2008.43.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Obesity during Anti-cancer Chemotherapy in Children with Acute Lymphoblastic Leukemia

Abstract: Background:We evaluated the pattern as well as the predictive factors of obesity in children with acute lymphoblastic leukemia (ALL) according to body mass index (BMI) changes that occur during anticancer chemotherapy. Methods: We reviewed the medical records of 58 patients who were diagnosed with ALL between 1995 and 2006 at the Department of Pediatrics at Hanyang University Hospital and Dong-A University Hospital. Five relapsed cases were excluded. The heights and weights of 55 children were measured at diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…One previous study also based on Korean children with ALL found a trend towards continued increase in BMI even after treatment completion19).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…One previous study also based on Korean children with ALL found a trend towards continued increase in BMI even after treatment completion19).…”
Section: Discussionmentioning
confidence: 89%
“…These results are in contrast to those of similar studies of obesity in childhood ALL patients who completed treatment with chemotherapy only, in which a significant portion of patients studied were found to be either overweight or obese at treatment completion 17 , 18) . One previous study also based on Korean children with ALL found a trend towards continued increase in BMI even after treatment completion 19) .…”
Section: Discussionmentioning
confidence: 89%
“…Otherinvestigators found metabolic syndrome is prevalent in 12.6-39% of childhood cancer survivors 10) . To date, very limited studiesin Korea have focused on the possible relationship between the treatment of childhood cancer and an increased risk of developing metabolic syndrome [11][12][13] . Moreover, most of these studies only include components of metabolic syndrome, such as obesity, or endocrine abnormalities.…”
Section: Metabolic Syndromementioning
confidence: 99%